The Postdiaspora Condition : Crossborder Social Protection, Transnational Schooling, and Extraterritorial Human Security - Laguerre, Michel S. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book aims to fill a void in the literature on the contributions of the state to the social protection, educational training, and human security of its overseas citizens. Additionally, Michel S. Laguerre seeks to explain the rise of the postdiaspora condition: an emancipatory metamorphosis of diaspora status. Laguerre pays particular attention to the crossborder services that the state provides, transfrontier mechanisms developed by various institutions, as well as extraterritorial forms of management and governance. He sheds light on complex crossborder arrangements and management, the multiplicity of crossborder agencies and organizations, and the promulgation of new laws that provide a legal basis for these extraterritorial undertakings by the state. The ability of emigrants to hold citizen status-and to enjoy access to the same rights and privileges as those offered to residents of the homeland-sets the cosmonational context for the performance of the postdiaspora condition. .
Keywords: Social sciences.; Ethnology.; Political sociology.; Emigration and immigration.; elektronické knihy; electronic books